Spiral organization of periodic structures in the Lorenz-Stenflo system - Rech P.C.* (2016)
© 2016 The Royal Swedish Academy of Sciences.This paper reports the existence of organized periodic structures embedded in chaotic regions of a parameter plane of the Lorenz-Stenflo system. More specifically, this work reports on spiral organization of periodic structures observed in the (σ, s) parameter plane of the Lorenz-Stenflo system.